Plenary Session IV: MEDICAL ETHICS: UNCOMMON MORALITY AND THE IMPLICATIONS FOR MEDICAL ETHICS EDUCATION - RHODES, Rosamond (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Common morality has been the touchstone for addressing issues of medical ethics since the publication of Beauchamp and Childress’s Principles of Biomedical Ethics in 1979. In my presentation, I will challenge that reigning view by presenting two arguments. The negative argument shows why common morality cannot be the ethics of medicine. The positive argument explains why medical professions require their own ethics. I will then explain medicine’s distinctive ethics in terms of the trust that society allows to the profession. By distinguishing roles from professions, I will explicate sixteen specific duties that medical professionals undertake when they join the profession. My derivation of medicine’s distinctive ethics begins with a thought experiment demonstrating that trust is at the core of medical practice. Society allows doctors to develop special knowledge and skills and allows them to employ special powers, privileges, and immunities that could be particularly dangerous to members of society. Society, therefore, has to be assured that professional’s use of their remarkable powers and privileges will be constrained to their intended use. Professions’ publically declared codes and oaths go a long way to engender public confidence in medical professionals. Medical education must complete the job by helping our trainees understand their professional obligations and become clinicians who uphold their profession’s ethics. Medical educators therefor have to help our students comprehend and internalize their duty to “seek trust and be deserving of it,” and uphold their fiduciary responsibility to “use medical knowledge, skills, powers and privileges for the benefit of patients and society.”